Explaining the pros and cons of different sources of Faculty Evaluation from the viewpoints of Medical University Academics - Ali Asghar Arabi Mianroodi; Zahra Asgari Baravati; Nages Khanjani (Kerman University of Medical Sciences, 2012)
Background & Objectives: Nowadays improvement of teaching quality is one of the basics for a credible higher education system and without doubt evaluation and monitoring of teaching quality are important for reaching this goal However different studies have shown that academic evaluation is one of the most controversial topics in Medical Education and deserves more research and attention Meanwhile the experience of academics as the subjects of these assessments can be very helpful Methods: The current study is a qualitative (phenomenology) study Interested academics were invited to participate in 4 focus groups each including 6 to 8 participants Open unstructured questions were asked Participants suggested different methods of academic assessment and commented on the pros and cons of each The focus group discussions ended when the conductors felt data saturation has been met Results : Data were analyzed through theme analysis method A total of nine different data sources including seven subjective sources (asking from students head of faculty head of department and colleagues as well as selfassessment twoway assessment and assessment by a third party) and two objective ones (students scoring and the academics output) were mentioned and their pros and cons were explored thoroughly and the methods for increasing data quality from each source were also proposed Conclusion: In order to acquire more fair results academic assessment should rather be done through an appropriate combination of different information sources and by considering the current situation and the shortcomings of each source